Chronic abruption in early second trimester mimicking partial mole - A rare case report (Indian Journal of Case Reports, 2018)
Placental abruption is known as one of the most serious complications in pregnancy with detrimental effect on both the mother and the fetus. The clinical presentation and the ultrasound findings of this condition vary to a large extent as can be depicted from our case report. We report a rare case of a 30-year-old, G3P2L2 at 4 months of gestation, who presented with the complaints of dark altered bleeding along with pain lower abdomen for 1 day. Ultrasound findings were a dead fetus of 19 weeks 2 days with diffusely enlarged placenta with multiple cystic areas suggestive of intrauterine demise with partial mole. This case report is important as chronic placental abruption in the second trimester is rare, and a high index of suspicion is imperative to differentiate it from other conditions such as partial mole.